Konstruksi Wacana Ekoteologi pada Website Resmi Kementerian Agama (kemenag.go.id): Analisis Wacana Kritis Norman Fairclough Januari 2026 - Atiyatul Mawaddah; Muhamad Farhan; Robiatul Adawiyah (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2026)
This article aims to analyze the discourse of ecotheology presented by the Ministry of Religious Affairs of the Republic of Indonesia through its official website during January 2026, using the critical discourse analysis framework of Norman Fairclough. The main focus of this study is to understand how ecotheology is represented, how power relations are constructed, and how identity is shaped within the discourse. This research employs a qualitative approach with critical discourse analysis techniques. The data were collected from 46 posts containing the keyword “ecotheology” on the official website of the Ministry of Religious Affairs, consisting of national and regional news as well as opinion articles. The analysis was conducted by dividing the discourse into three main dimensions: microstructural, mesostructural, and macrostructural. The findings reveal that at the microstructural level, ecotheological discourse is represented through the use of strong theological diction such as amanah (trust), khalifah (stewardship), and responsibility of faith, which construct a religion-based ecological awareness while reinforcing power relations by positioning the Ministry of Religious Affairs as the primary authority. At the mesostructural level, the Ministry’s website functions as an institutional medium that dominantly produces and distributes discourse, where journalists tend to be part of the organizational structure, thereby reinforcing a single narrative without presenting critical perspectives. Meanwhile, at the macrostructural level, ecotheological discourse emerges as a strategic response to global and national environmental crises, as well as part of efforts to integrate religious values into sustainable development, including within the context of international diplomacy. This study confirms that the Ministry of Religious Affairs utilizes its digital platform as a primary medium to construct and disseminate ecotheological discourse as part of a transformation of religiosity oriented toward environmental awareness. The analysis also demonstrates that representation, power relations, and identity formation within ecotheological discourse play a significant role in shaping collective awareness of the importance of environmental preservation as an integral part of religious practice.